Using FAIR metadata for secondary use of administrative claims data - Haux, Christian; Knaup-Gregori, Petra (MEDINFO 2019, 2019)
The FAIR principles require the reporting of rich metadata. However, when researchers use data for secondary use from external data owners, the FAIR principles require a different implementation as if the researchers would describe their own data. In this paper, we specify how FAIR metadata can be implemented for secondary data analyses and provide a suggestion for relevant metadata.
Gesehen am 08.12.2020